Q: What is 5 yd 1 ft minus 3 yd 2 ft?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

52 yd 1 ft - 17 yd 2 ft = 51 yd 4 ft - 17 yd 2 ft = 34 yd 2 ft

38 feet

3 yd 1 ft

7 yd 1 ft - 5 yd 2 ft = 22 ft - 17 ft = 5 ft = 1 yd 2 ft.

5yd 3ft

Related questions

52 yd 1 ft - 17 yd 2 ft = 51 yd 4 ft - 17 yd 2 ft = 34 yd 2 ft

38 feet

3 yd 1 ft

1 yd. 2 ft.

7 yd 1 ft - 5 yd 2 ft = 22 ft - 17 ft = 5 ft = 1 yd 2 ft.

5yd 3ft

9 yd 2 ft. Incidentally, 2 yd 4 ft is a strange way of representing a distance of 3 yd 1 ft.

There are 3 ft in a yd ...[(9 x 3 = 27) + 1] - [(4 x 3 = 12) + 2] = (28 - 14) = 14 ft OR 4 yd 2 ft

14 feet or 4 yd 2 ft

4 ft 1 in

3 ft = 1 yd → 5 ft = 1 yd 2 ft → 8 yd + 5 ft = 8 yd + 1 yd 2 ft = 9 yd 2 ft.

The Answer is 2 yd 9 ft because its like 51-22=29